MOUNTING PROBLEMS IN GLOBAL ECONOMY AND FINANCIAL SYSTEM (British Journal of Global Ecology and Sustainable Development, 2023)
This article covers a number of problems in the world economy at the moment, as well as several ways aimed at eliminating them. The information system, which is currently developing rapidly, also certainly has an impact on the development of the economy. Therefore, opinions are given about the role of the information and communication system in the development of the economy and what should be paid attention to when solving problems.